Re-positioning the competences of beginner teachers in South Africa: A capabilities perspective - Esau, D.E.; Maarman, R. (South African Journal of Higher Education, 2020)
On entering the teaching profession, beginner teachers in South Africa are expected to comply with requirements underlying the National Policy Framework for teacher education in South Africa (NPF 2006). These requirements are stipulated as follows: A teacher needs to be a specialist in a particular learning area, subject or phase; a specialist in teaching and learning; a specialist in assessment; a curriculum developer; a leader, administrator and manager; a scholar and lifelong learner; and a professional who plays a community, citizenship, and pastoral role.Recent studies have however revealed that there are many concerns among newly appointed teachers about their readiness to fulfil these roles. This has lead us to do an explorative investigation in an effort to re-position the capabilities of beginner teachers. The qualitative data extrapolated from a literature investigation, teacher education policy and semi-structured interviews will guide us in formulating findings, pertinent to establishing a support strategy in what they deem as the most challenging aspects in and around the classroom. The investigation is underpinned by Sen’s (1980) capabilities approach which offers a yet unexplored lens through which to understand the importance of supporting beginner teachers to think critically and creatively, solve problems, make informed decisions, cope with and manage new situations, and communicate effectively in order to deal with new situations as it may arise in the classroom on a daily basis (Maarman 2009, 321).